Increasing the treatment motivation of patients with somatic symptom disorder: applying the URICA-S scale - Mander, Johannes; Schaller, Georg; Bents, Hinrich; Dinger, Ulrike (BMC psychiatry, 2017)
Therapeutic intervention programs for somatic symptom disorder (SSD) show only small-to-moderate effect sizes. These effects are partly explained by the motivational problems of SSD patients. Hence, fostering treatment motivation could increase treatment success. One central aspect in SSD patients might be damage to motivation because of symptomatic relapses. Consequently, the aim of the present study was to investigate associations between motivational relapse struggle and therapeutic outcome in SSD patients.
Gesehen am 15.02.2018